Synthesis, characterization, and thermophysical properties of 1,8-diazobicyclo5.4.0undec-7-ene based thiocyanate ionic liquids - Lethesh, K.C. (American Chemical Society, 2014)
In this work, synthesis of 12 ionic liquids based on 1,8-diazobicyclo5.4. 0undec-7-ene (DBU) cation with anions such as chloride, bromide, and thiocyanate were performed. The new ionic liquids were characterized using nuclear magnetic resonance spectroscopy and elemental analysis. The effect of alkyl spacer length on the physicochemical properties of DBU based ionic liquids was studied by attaching ethyl, butyl, hexyl, octyl, decyl, and tetradecyl groups to the DBU cation. The effects of temperature on the density and viscosity over a temperature range from 293.15 K to 373.15 K were recorded at atmospheric pressure. From the experimental density values, the thermal expansion coefficient values were calculated. The surface tension of the neat ionic liquids was measured at seven different temperatures (293.15 K, 303.15 K, 313.15 K, 323.15 K, 333.15 K, 343.15 K, and 353.15 K). The surface entropy and surface enthalpy were calculated from the experimental surface tension value at 303.15 K. The thermal behavior of these ionic liquids was studied using thermogravimetric analysis and differential scanning calorimetry. Â© 2014 American Chemical Society.